Social evaluation of the youth behavior and value sphere in Namangan region - Mirzatov , Baxtiyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The main hypothesis of the current study is that human values are related to the level and quality of economic activity. Having studied the nature of value orientations, it can be assumed that value orientations can determine a person’s behavior in the labor market, that is, the level of economic activity. Statistical indicators of the economy of the Namangan region and the state of the labor market are the main source of scientific observations, predictions, analytical reports, etc.